1995
DOI: 10.1016/s0969-2126(01)00169-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the X-ray structures of HIV-1 and HIV-2 proteases in complex with CGP 53820, a novel pseudosymmetric inhibitor

Abstract: Minor sequence changes in subsites at the active site can explain some of the observed differences in substrate and inhibitor binding between the two enzymes. The information gained from this investigation may help in the design of equipotent HIV-1/HIV-2 protease inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 40 publications
5
86
0
Order By: Relevance
“…Although they have similar structures (40), HIV-2 and HIV-1 proteases are approximately 50% divergent in their amino acid compositions (21). Moreover, differences in conformation (32) and interaction parameters with substrates or PI have been described (15,29,43). It is important to know if natural polymorphism and mutations which confer resistance to PI in HIV-1 are found at homologous positions in the HIV-2 protease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they have similar structures (40), HIV-2 and HIV-1 proteases are approximately 50% divergent in their amino acid compositions (21). Moreover, differences in conformation (32) and interaction parameters with substrates or PI have been described (15,29,43). It is important to know if natural polymorphism and mutations which confer resistance to PI in HIV-1 are found at homologous positions in the HIV-2 protease.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies, abstr. 32,2002). To date, only one study has reported the presence of genotypic changes in the protease gene of HIV-2 which could be drug resistance-associated mutations (34).…”
mentioning
confidence: 99%
“…This mutation has also been reported to affect sensitivity to some PR inhibitors (51). In the simian immunodeficiency virus SIVmac and HIV-2 PRs, position 47 is naturally occupied by valine, but in these cases the position 32 residue is isoleucine rather than the valine found in the HIV-1 PR; this may represent a compensatory mutation since in each case the ␦ carbon of the isoleucine (Ile-47 of HIV-1 and Ile-32 of SIVmac and HIV-2) is in approximately the same position (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…This transition-state mimic offered several advantages over other isosteres including the elimination of a chiral center by replacement of the carbon bearing P 1 0 substi- tuent and access to a broad range of substituents by simple acylation chemistry. Initial optimization studies were based on X-ray crystal data of an aza-peptide inhibitor in complex with HIV PR [108]. Variations of R 1 (see Fig.…”
Section: Drug Optimizationmentioning
confidence: 99%